Digital Leadership and Employee Digital Performance: The Mediating Roles of High Involvement Human Resource Practices and Dynamic Capability - Rafanjamalala Benjamine Andreas; Naelati Tubastuvi; Suryo Budi Santoso; Bima Cinintya Pratama (Universitas Muhammadiyah Sorong, 2026)
Digital transformation has become a strategic priority for higher education institutions seeking to improve organizational effectiveness and employee performance. However, previous studies have largely examined digital leadership, HRM practices, and employee capability separately, providing limited understanding of how digital leadership improves employee digital performance. Therefore, this study investigates the indirect effect of digital leadership on employee digital performance through High-Involvement Human Resource Management Practices (HI-HRMP) and employee dynamic capability. This study draws on the Resource Based View Theory (RBV), and Dynamic Capability Theory (DCT) to suggest that digital leadership has a positive effect on the adaptive capabilities of employees, organizational HR practices, and outcomes of digital work. The data were obtained from 205 academic and administrative staff in one private university in Indonesia through questionnaires (online and paper), and further analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that digital leadership does not directly influence employee digital performance. Instead, its effect occurs indirectly through HI-HRMP and employee dynamic capability. This study contributes to the digital leadership literature by explaining the organizational and individual mechanisms linking leadership and digital performance in higher education institutions.